Open femorotibial dislocation with fracture of the patella and tibia - José Luis Nápoles Mengana (ECIMED, 2021)
Introduction: Knee dislocations are infrequent, which makes the combination with open fractures of the patella and the upper third of the tibia, rare and serious. It is an entity caused by high-energy trauma and is associated with other injuries. Objective: To present a rare and complex case of open posterior femorotibial dislocation with fracture of the lower pole of the patella and the upper third of the tibia. Clinical case: A 37-year-old male patient, who was admitted to the orthopedic and trauma service, who, as a consequence of a traffic accident, presented posterior femorotibial dislocation with an open fracture of the lower pole of the patella and upper third of the tibia. grades III-B, in the lower right. He underwent emergency surgery; extensive surgical debridement, dislocation reduction, primary repair of ligamentous injuries, partial patellectomy, patellar tendon repair, and external fixation were performed for the fracture of the upper third of the tibia. The patient evolved well, without infection of the surgical wound and full recovery at 4 months. Conclusions: The combination of open posterior femorotibial dislocation, with fracture of the lower pole of the patella and upper third of the tibia is rare and is due to high traumatic energies, such as motor vehicle accidents. Emergency surgery and antimicrobial prophylaxis is the effective method for the definitive treatment of this lesion.